ARCHAEOMETRIC STUDY OF GLASS BEADS FROM SAN BARTOLOMÉ DE LOS CHANÁ (SANTA FE, ARGENTINA). HOW FAR CAN WE GO? - Lambri, Melania (Centro de Estudios de Arqueología Histórica (CEAH) de la Universidad Nacional de Rosario, 2024)
San Bartolomé de los Chaná (SBCH) is a historic colonial site from the 17th century, located at the mouth of Monje Creek (Santa Fe, Argentina). A Franciscan Indian reduction founded by Hernando Arias de Saavedra (Hernandarias) and under the responsibility of an encomendero from Santa Fe la Vieja was established there. The materiality of this site is expressed in "La Boca"; exhibiting a wide range of items that show the interethnic situation of the "life in police" during the conquest and colonization of the Paraná coast. This work will focus on the collection of Venetian beads recovered at this site, which were first studied at a macroscopic and typological level by De Grandis and Rocchietti in 1997. The need to deepen the knowledge of the possible nature of origin and use given to this type of objects motivated that they began to be studied archaeometrically in recent years. For this reason, we propose to present here the results obtained through the analysis with optical microscopy, x-ray fluorescence and computed tomography on three pieces from this collection. These results have allowed us to advance in the tasks of verifying and obtaining more information on: i) the physicochemical and compositional qualities of the pieces (associated to the possible raw materials and manufacturing techniques used for their elaboration) and ii) how they were affected by the different types of processing techniques used.